Differences in Multisensory Comfort Across Five Public Outdoor Functional Spaces: Evidence from an Autumn Field Study in Dalian, China - Bingru Chen; Xinjie Li; Shengqi Deng; Ting Li; Hongchi Zhang (Buildings, 2026)
Outdoor comfort is influenced by thermal, visual, and acoustic stimuli, whose relative roles may vary across functional spaces. This study compared multisensory comfort characteristics across five frequently used public outdoor functional spaces in the main built-up area of Dalian, China, during the autumn transition season and examined their associations with overall comfort. Rotational fixed-point monitoring and synchronous questionnaire surveys were conducted in residential, cultural, educational, commercial, and green spaces, yielding 1497 valid responses. The results showed that: (1) Among the five investigated public outdoor spaces, the residential space had the highest proportion of positive overall comfort votes, whereas the educational space showed more thermal discomfort and negative acoustic evaluations. (2) Thermal and acoustic sensations changed linearly with corresponding exposures, while visual comfort first increased and then decreased with illuminance. (3) Thermal comfort had the largest main effect on overall comfort, visual comfort was also significant, and thermal–acoustic interaction was observed. (4) SEM indicated distinct association pathways. The thermal pathway showed a significant serial indirect effect through thermal sensation and thermal comfort, while the visual pathway contained indirect effects in opposite directions and the acoustic pathway was characterized mainly by a direct negative association between LAeq and overall comfort. These findings support function-sensitive multisensory assessment and targeted outdoor environmental optimization.